Mechanical properties measurement of materials and devices at micro- and nano-scale by optical methods: A review. (March 2022) - Liu, Mengxiong; Li, Xide
Highlights: This paper detailly reviews the progress of optical techniques developed for measuring mechanical properties of materials and devices at micro- and nano-scale. The development of testing systems, including the equipment, clamping and loading are reviewed. The deformation carries are reviewed, especially for the special materials and structures, such as the ultra-long carbon nanotubes and interface. The principle, progress and typical application of the optical methods are reviewed, including the holography, speckle and moiré. The new challenges and the possible directions of developing new methods are discussed. Abstract: In the past three decades, we have witnessed the explosive development of micro/nano science and technology, where remarkable research efforts have been made in synthesizing of materials and fabricating of devices at micro- and nano-scale. The unusual mechanical behaviors of materials and devices with reduced their size and dimension pose the open questions to the researchers, which expand the framework of mechanics by advancing the theory, as well as modeling and experimental tools. Researchers in worldwide have been actively involved into this exciting area, making remarkable contributions to measure mechanical parameters and understand the mechanical behaviors of materials and devices at micro- and nano-scale. Micro optical method, as a full field, real-time and non-destructive measurement technique, is one of the earliest techniques used to measure the mechanical properties of materials at micro scale. So far, the optical methods are still an exciting research area in the field of mechanical property measurement of materials and devices at such small scale, even with the further reduction of the size of the research materials and devices, and their experimental platform has been promoted to various scanning microscope platforms, such as scanning electron microscope (SEM), scanning transmission electron microscope (STEM), atomic force microscope (AFM) and so on. This article reviews the research progress of optical techniques developed for the measurement of mechanical properties of materials and devices at micro- and nano-scale, with the aim to clarify the measurement principles and applications of optical methods in small scale, consisting of the experimental equipment, clamping and loading, deformation carriers or marks, optical methods including the holography, speckle and moiré, and finally to outline the perspectives in this fast-evolving field.